2011
DOI: 10.1530/jme-11-0127
|View full text |Cite
|
Sign up to set email alerts
|

Normalizing action of exendin-4 and GLP-1 in the glucose metabolism of extrapancreatic tissues in insulin-resistant and type 2 diabetic states

Abstract: Exendin-4 (Ex-4) mimics glucagon-like peptide-1 (GLP-1 or GCG as listed in the HUGO database), being anti-diabetic and anorectic, in stimulating glucose and lipid metabolism in extrapancreatic tissues. We studied the characteristics of Ex-4 and GLP-1 action, during prolonged treatment, on GLUTs expression (mRNA and protein), glycogen content (GC), glucose transport (GT), glycogen synthase a (GSa), and kinase (PI3K and MAPKs) activity, in liver, muscle, and fat of insulin-resistant (IR, by fructose) and type 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 55 publications
0
20
0
3
Order By: Relevance
“…Most importantly, incretins are known to stimulate insulin secretion during hyperglycemia. In addition, glucagon secretion may be reduced, and some studies have suggested that incretins may have direct effects on tissues such as the liver, increasing insulin sensitivity (1,10,26) and modifying molecular regulators of hepatic glucose metabolism (3,14,15,45,54), thereby modifying liver glucose production and uptake independently from the effects of changes in insulin secretion. On the other hand, other studies have not observed a direct effect (1,10,26), and our data support the latter conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most importantly, incretins are known to stimulate insulin secretion during hyperglycemia. In addition, glucagon secretion may be reduced, and some studies have suggested that incretins may have direct effects on tissues such as the liver, increasing insulin sensitivity (1,10,26) and modifying molecular regulators of hepatic glucose metabolism (3,14,15,45,54), thereby modifying liver glucose production and uptake independently from the effects of changes in insulin secretion. On the other hand, other studies have not observed a direct effect (1,10,26), and our data support the latter conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Ex-4 has been shown to increase liver glucokinase activity in hepatocytes isolated from diabetic mice in an insulin-independent manner (14,15). In addition, GLP-1 and Ex-4 have been reported to increase glycogen accumulation in rat hepatocytes, an effect associated with increased and decreased glycogen synthase and phosphorylase activities, respectively (3,45,54), although others were unable to reproduce those results (47). In vivo, in response to physiological GLP-1 infusion in humans and dogs, some studies have identified insulin-independent increases in glucose uptake, including by the liver (11,12,22,48), whereas others have not (50,57).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a functional component of the nuclear pore complexes, considering that nuclear pore complexes have been reported to contribute to the generation of dentin [75], it is reasonable to summarize that NUP153 is definitely a co-regenerative gene for both dentin and vessel [84]. GCG (ENSP00000387662) has been widely reported to contribute to glucose metabolism and homeostasis [85,86]. According to recent publications, GCG has been confirmed to enhance the dentin bio modification potentials, implying its potential functions during dentin regeneration [87].…”
Section: Co-regeneration Genes For Dentin and Vesselmentioning
confidence: 99%
“…Membrane samples were prepared from the liver cells and muscles according to available method (Moreno et al, 2012). Membrane samples were stored at-70°C for analysis.…”
Section: Isolation Of Membranementioning
confidence: 99%